EPID-05. PREDIAGNOSTIC SYMPTOMS AND SIGNS OF ADULT GLIOMA: THE PATIENTS' VIEW. (11th November 2019) - Peeters, Marthe; Dirven, Linda; Koekkoek, Johan; Gortmaker, Ellen; Fritz, Lara; Vos, Maaike; Taphoorn, Martin
Abstract: BACKGROUND: Little is known about the symptoms/signs glioma patients experience in the year before diagnosis, either or not resulting in health care usage. The objective of this study was to determine the incidence of symptoms/signs glioma patients experienced in the year prior to diagnosis, as well as visits to a general practitioner (GP) related to these issues. METHODS: Glioma patients were asked to complete a 30-item study-specific questionnaire, if possible with input of a proxy, focusing on symptoms and signs they experienced in the 12 months before diagnosis. For each indicated symptom/sign, patients were asked whether they consulted the GP for this issue. RESULTS: Between July 2016 and April 2019, 59 patients completed the questionnaires, 54 (93%) with input of a proxy. Forty (68%) patients were men, with a median age of 60 years and the median time since diagnosis was 4 months (range 1–12). The median number of symptoms/signs experienced in the year before diagnosis was 9 (range 2–19) in low-grade and 5 (range 0–24) in high-grade glioma (p=0.230). The five most frequently mentioned problems were fatigue (34, 58%), mental tiredness (30, 51%), sleeping disorder (24, 41%), headache (23, 39%) and stress (20, 34%), with no differences between low- and high grade glioma. Twenty-six (44%) patients had visited the GP with at least one issue. We found that patients who did consult their GP reported significantly more often muscle weakness (11 vs 3, p =0.003) than patients who did not, which remained significant after correction for multiple testing, which was not the case for paralysis in hand/leg (10 vs 4), focussing (11 vs 6) or a change in awareness (9 vs 4). CONCLUSIONS: Glioma patients experience a range of problems in the year prior to diagnosis, but patients who consult the GP report significantly more often neurological problems.